2022
DOI: 10.1038/s41598-022-13846-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and characterisation of commensal wild birds and their interactions with domestic ducks on a free-range farm in southwest France

Abstract: The role of commensal birds in the epidemiology of pathogens in poultry farms remains unclear. Our study aimed to identify potential key species for interactions with domestic ducks on one free-range duck farm in southwest France. Methods combined direct individual observations on duck outdoor foraging areas, network analysis, and general linear mixed models of abundances. Results showed a wide diversity of wild bird species visiting foraging areas, heavily dominated in frequency by White wagtails (Motacilla a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Also, European starlings, a species closely related to the spotless starling have been experimentally shown to be able to transmit avian influenza virus to poultry ( 40 ). Species detected in free-range layer farms such as the white wagtail are consistent with the species detected in a study of free-living birds in enclosures of duck farms in France ( 5 ), while other species observed on the duck farms, such as cattle egrets, were observed less frequently.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Also, European starlings, a species closely related to the spotless starling have been experimentally shown to be able to transmit avian influenza virus to poultry ( 40 ). Species detected in free-range layer farms such as the white wagtail are consistent with the species detected in a study of free-living birds in enclosures of duck farms in France ( 5 ), while other species observed on the duck farms, such as cattle egrets, were observed less frequently.…”
Section: Discussionsupporting
confidence: 84%
“…However, although bidirectional exchange of pathogens at the interface has been demonstrated and the potential of bridge hosts is generally accepted ( 36 ) little information exists yet on the frequency of contact and potential of contamination of resident farm birds by visiting migratory birds. For this reason we used the pictures obtained to also study the contact of wild birds that visit farm premises, but are unlikely to enter the buildings and enclosures, with the house sparrow ( 4 , 5 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mixed confinement system creates conditions that increase the opportunity for contact between poultry of different flocks, and as shown in the results, increase their interactions with wild birds, and consequently, the risk of contamination and spread of diseases. Previous studies have already suggested that contact at the wild-domestic bird interface is more likely in free-range farming systems [19,31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one important question that should now be addressed is related to the impact of palmiped flock size on virus transmission risk. Additionally, during their first production stage, ducks raised for foie-gras have access to large outdoor fields, where they can have direct and indirect contacts with commensal wild birds [ 24 ] as well as with neighbouring farms via the environment, potentially contributing to the diffusion of HPAI viruses. However, the impact of outdoor grazing on the virus transmission dynamics still has not been clarified, mainly due to the unavailability of relevant data at the time the model of the 2016–2017 epidemic was developed.…”
Section: Discussionmentioning
confidence: 99%